2020
DOI: 10.1186/s12888-020-02809-4
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia patients with a metabolically abnormal obese phenotype have milder negative symptoms

Abstract: Background: Schizophrenia patients with a metabolically abnormal obese (MAO) phenotype have been shown poor cardiovascular outcomes, but the characteristics of their current psychiatric symptoms have not been characterized. This study mainly explored the psychiatric symptoms of schizophrenia patients with the MAO phenotype. Methods: A total of 329 patients with schizophrenia and 175 sex-and age-matched people without schizophrenia from Anhui Province in China were enrolled. The Positive and Negative Syndrome S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…However, compared with the other two studies, BMI, LDL-C, FPG, and SUA/Scr ratio levels were lower in the present cross-sectional study (Table 1 , Table S2). The reason was considered to be related to the limitation of the present cross-sectional study to the non-obese population with a normal range of LDL-c. Studies have reported that the SUA/Scr ratio level was positively correlated with BMI and LDL-c [ 36 ], and FPG was positively correlated with BMI and LDL-c [ 61 ]. The findings of our study extend the existing literature that the SUA/Scr ratio increases the risk of NAFLD regardless of whether participants had normal or abnormal levels of BMI, LDL-c, FPG, SUA, etc.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared with the other two studies, BMI, LDL-C, FPG, and SUA/Scr ratio levels were lower in the present cross-sectional study (Table 1 , Table S2). The reason was considered to be related to the limitation of the present cross-sectional study to the non-obese population with a normal range of LDL-c. Studies have reported that the SUA/Scr ratio level was positively correlated with BMI and LDL-c [ 36 ], and FPG was positively correlated with BMI and LDL-c [ 61 ]. The findings of our study extend the existing literature that the SUA/Scr ratio increases the risk of NAFLD regardless of whether participants had normal or abnormal levels of BMI, LDL-c, FPG, SUA, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the rationale above that SGAs likely affect different receptor systems based on the dose used, and may have therapeutic properties for anxiety and depression at lower doses. In contrast, based on data from multiple studies, chlorpromazine equivalents for people with schizophrenia were mostly greater than 400 mg/day [33][34][35]. When looking at specific antipsychotics in our sample, this principle held up.…”
Section: Discussionmentioning
confidence: 75%
“…The form, which was prepared by the researcher by scanning the literature (Holt, 2019, Annamalai et al 2017, Wang et al 2020, includes information about patients' sociodemographic characteristics, disease and treatment.…”
Section: Personal Information Formmentioning
confidence: 99%
“…Metabolic syndrome is 4 times more common in patients with schizophrenia who use atypical antipsychotics than in the healthy population (Demirel et al 2015). Patients with schizophrenia are known to be unable to consume an adequate and balanced diet (Wang et al 2020) and engage in sufficient physical activity due to their lower socioeconomic status, lower education level, and non-optimal living conditions (Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%